Исследования распределения концентрации ионов при использовании импульсного коронного разряда для зарядки тонкодисперсной фазы аэрозоля - Пустовой, Дмитрий Сергеевич; Чеберячко, Иван Михайлович (НТУ "ХПИ", 2017)
Проанализированы вопросы процессов электроионизации при использовании импульсного коронного разряда, а также предложена система коронирующих электродов типа «острие – сетка». Установлена зависимость концентрации аэроионов от расстояния до ионизатора, позволяющая устанавливать заданный ионный состав для накопления максимально возможной величины заряда на мелкодисперсных частицах, однако скорость воздушного потока ограничивается технологическими параметрами и ее значения определяются в зависимости от условий (конструкции технологического оборудования, типа аспирационной системы и др.), а величина напряжения импульса ограничивается параметрами зарядного устройства при которых исключается «пробой».

The paper considers problems of electroionization processes while applying pulse corona discharge; in addition, a system of corona producing devices of “point-net” type has been proposed. A dependence of concentration of air ions from distance to ionizer has been determined. The dependence makes it possible to identify the preset ionic composition to accumulate maximum possible charge value within fine-dispersed particles, but the airflow velocity is limited by technological parameters and its values are determined depending on conditions (technological equipment, etc.), and the magnitude of the impulse voltage is limited by the parameters of the charger at which the "breakdown" is excluded. Also on the basis of the studies carried out, a device for generating a high voltage voltage pulse is proposed, which makes it possible to intensify the ionization of the medium in the interelectrode space and at the moments of a pause between the voltage pulses, to ensure the outflow of the ions formed beyond the discharge gap by the moving dust and gas environment.
Analysis of electroionization processes while applying pulse corona discharge to charge finely dispersed aerosol phase
Keywords: электроионизация; напряжение; камера зарядная; коагуляция; electroionization; pulse corona discharge; pulse voltage; aerosol; charging chamber; coagulation